Experiences of facilitators regarding the extended curriculum programme offered at a higher education institution in the province of KwaZulu-Natal in South Africa - Maureen N. Sibiya; Hazel T. Mahlanze (AOSIS, 2018)
Background: Much like the rest of the world, student access and success are primary concerns of the South African higher education institutions, especially in the face of data that suggest that up to 50% of students do not successfully complete their course of study. Despite compulsory and free basic education for all South Africans, and increased government funding for education, there has been little impact on learner performance and the majority of primary schools remain poor. To improve access and success and in keeping with international practice, the Department of Nursing at the selected university of technology in 2013 offered for the first time the extended curriculum programme (ECP). To date, the impact of the programme has never been evaluated. Objectives: The aim of the study was to explore the experiences of the facilitators regarding ECP in the undergraduate nursing programme. Method: Guided by this, the current article describes a qualitative exploration of the experiences of six purposively selected facilitators regarding ECP in the Department of Nursing. In-depth interviews were conducted with the ECP facilitators. Tesch's method was used to analyse the data. Results: Four main themes emerged from the data: stigmatisation and lack of confidence, lack of self-will, additional workload of facilitators and gradual improvement of students' performance. The participants reported that although students displayed and verbalised negative attitude towards the ECP, the performance of students showed gradual improvement and thus a need to continue to offer the programme to increase access and success in higher education institutions. Conclusion: It was concluded that ECP should continue to increase access and success in higher education institutions; however, there is a need for additional resources to support ECP students.